The Effect Of Medium Of Language On Mathematics Achievement - A Comparison Study - Chhan, Siew Lan (Universiti Malaysia Sarawak, (UNIMAS), 2008)
The study aimed to identify the effect of medium of language on students 'Mathematics achievement. Two sets of Mathematics question papers in two versions namely English version and Bahasa Malaysia version as well as a set of questionnaire were used as research instrument. A total number of 70 set of Mathematics question papers and 70 set of questionnaire were distributed to Primary Five and Form Two students respectively. The psychometric analysis consist of factor analysis and Croncbach Alpha test. Factor analysis was used to fest the validity of the questionnaire while Croncbach Alpha was used to test the reliability of the questionnaire. The collected Mathematics question papers and questionnaires were analyzed using the Statistical Package for Social Sciences version 14.0 (SPSS 14.0). Paired-sample T-test was used to compare the Mathematics achievement of Primary Five and Form Two students respectively in English and Bahasa Malaysia. Independent sample T-test was used 10 compare the Mathematics achievement between primary and secondary school's students. Pearson correlation analysis was used to determine the relationship between students' perception towards their English language ability and their Mathematics achievement. This study found that there is a significant difference in the Mathematics achievement of Primary Five students in English and Bahasa Malaysia. This study also found that there is a significant difference in the Mathematics achievement of Form Two students in English and Bahasa Malaysia. Moreover, there is a Significant difference in the Mathematics achievement between primary and secondary school's students. Both Prim01Y Five and Form Two students' perception towards their English language ability had positive relationship with their Mathematics achievement.